2017
DOI: 10.1007/s00417-017-3631-z
|View full text |Cite
|
Sign up to set email alerts
|

Implication of VEGF and aquaporin 4 mediating Müller cell swelling to diabetic retinal edema

Abstract: The observed Müller cell swelling is mediated by VEGF and AQP4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…Our in vitro study mimicked our in vivo study in that high glucose condition increased the cellular volume and TGN-020 depressed the increase. We previously showed that TGN-020 depressed the VEGF-induced cellular swelling of TR-MUL5 cells, indicating that VEGF-induced increase of cellular volume is mediated by AQP4 [22]. Consistently, high glucose condition caused swelling of Müller cells, and ROS was increased in these cells.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our in vitro study mimicked our in vivo study in that high glucose condition increased the cellular volume and TGN-020 depressed the increase. We previously showed that TGN-020 depressed the VEGF-induced cellular swelling of TR-MUL5 cells, indicating that VEGF-induced increase of cellular volume is mediated by AQP4 [22]. Consistently, high glucose condition caused swelling of Müller cells, and ROS was increased in these cells.…”
Section: Discussionmentioning
confidence: 57%
“…AQP4 would also be involved in diabetic retinal edema through vasogenic and cytotoxic mechanisms. Recently, we reported the possibility that AQP4 and VEGF are involved in Müller cell swelling, using diabetic rats and cultured Müller cells [22]. To our knowledge, there is no report related with ROS and AQP4 in diabetic rat retinas.Taken together, it seems that VEGF, ROS, and AQP4 are closely linked in the retina, and that the unbalance between them may contribute to the development of diabetic retinopathy and DME.Several chemical structures with an AQP4 inhibitory effect have been identified.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We did not have plausible explanation for the difference. The positive relationship between the INL thickness and HbA1c levels might be due to the hyperglycemia-induced swelling of Müller cells (36). The HbA1c levels negatively affected the thickness of photoreceptors and positively affected that of the inner retinal layers and RPE.…”
Section: Discussionmentioning
confidence: 97%
“…31 It has been reported that the absorption of fluid from the inner retinal tissues is through the AQP4 channels, and retinal ischemia downregulates the activity of AQP4. 32 This then impairs the fluid clearance leading to retinal edema. 32 We have confirmed that the retinal edema was due to the upregulation of VEGF and the downregulation of AQP4 in the mouse RVO model.…”
Section: Expression Level Of Aqp4 Is Significantly Increased By Earlymentioning
confidence: 99%